Consistency of plant species and trait responses to grazing along a productivity gradient: a multi-site analysis - Pakeman, R.J (The Journal of ecology, 2004)
1. Studies of the responses of communities to land use or climate change at a functional rather than species level have used species traits as response or effect variables to enable generalization between different communities and biogeographical regions. Data from 10 published experiments on semi-natural and agricultural grasslands in Scotland, and from published information on plant traits, were used to determine whether (a) species and trait attributes behave consistently with respect to changing grazing intensity at sites of different productivity and (b) whether species and attribute responses to grazing were affected by site productivity. 2. Only 9 out of 22 species common enough to show a consistent response to grazing did so. For example, Deschampsia flexuosa and Molinia caerulea declined when grazing intensity increased, whilst Anthoxanthum odouratum and Cerastium fontanum increased. A similar proportion (12/29) of traits behaved consistently between studies. 3. Increased grazing intensity was accompanied by an increase in species with a ruderal strategy, an annual life history, seasonal regeneration by seed, flowering and seed dispersal early in the season, rosette habit, higher requirement for light and a lower minimum height. 4. The response of five species was modified by site productivity. In four cases, the effect was to modulate the rate of response to grazing change. In contrast, Nardus stricta increased with grazing at low productivity sites, but decreased at high productivity sites. Many more traits (22), including attributes related to life history, life form, and vegetative and sexual reproduction, showed a response to grazing modulated by productivity. Eight of these changed in a complex manner, akin to that of N. stricta. 5. The response of some species and traits to grazing appears predictable. However, for some species and many traits either the rate or the direction of response is controlled by the productivity of the vegetation.